A place-based alternative approach to food security: lessons learned from a neighborhood house. (15th March 2018) - Yan, Miu Chung; Sutherland, Rory
Abstract: The urban poor in many advanced economies have become subject to the problem of food security. So far, the charity food model, such as foodbanks and meal programs, has been the key solution to this problem. This model tends to undermine service users' aspirations to eat healthy food and their agentic function for change. Using a case study approach, we examine how a place-based community organization, with roots in the settlement house tradition, adopts an alternative approach to food security issues in an impoverished neighborhood. Adopting an activist and a right-to-food philosophy, it has brought together local residents to collectively tackle prevalent hunger and unhealthy food supply problems in the community.